Effects of Slag-Based Fertilizer to Mitigate Salinity Stress on Greenhouse Durum Wheat (Triticum Durum Desf.) Cultivars - Farid Errouh; Abdelhamid Aouabe; Ayoub Sadouki; Hassan Chagiri; Hicham Khalisse; Brahim Oudra; Julio Cesar Rodriguez; Salah Er-Raki; Abdelilah Meddich (European Scientific Journal, ESJ, 2023)
For a modern agricultural, the search for sustainable practices to increase productivity is fundamental. Steel slag have been studied for their potential use in agriculture. These substances present a great possibility of agricultural applications since they are rich in nutrients, which enhance plant uptake. In this regard, the effect of steel slag based-fertilizer was investigated in the greenhouse durum wheat cultivation in pots under salt-stress conditions. Two slag doses: 10 g slag/ kg soil (D1) and 20 g slag/ kg soil (D2) were evaluated under no salt-stress (0 mM NaCl) and salt-stress conditions (100 mM NaCl) for salinity stress mitigation. Morpho-physiological and biochemical parameters of wheat were measured and compared to the different treatments. Wheat exposure to salinity decreased its biomass, stomatal conductance, efficiency of photosystem II, protein content and increased total soluble sugars, hydrogen peroxide (H2O2) and malondialdehyde (MDA) contents. Amended plants with 10 g slag/ kg soil (D1), led to a significant improve in biomass with an increase of shoot and root dry weights (133% and 400% respectively), stomatal conductance (22 %), soluble sugars (14 %) and protein content (158%) under salinity conditions as compared to the control treatment 0 g slag/ kg soil (C), indicating a positive influence on durum wheat plants. However, soil enrichment with 20 g slag/ kg soil (D2) decreased plant growth parameters and presented the highest levels of H2O2 and MDA contents compared to the control and treatment D1 after three months of cultivation under salt-stress. This study supports the hypothesis of the application of slag at lower dose improve productivity of durum wheat and mitigate salinity stress.